Perpetua's passion : the death and memory of a young Roman woman - Salisbury, Joyce E. (Routledge, 1997)
Tells the story of Vibia Perpetua's arrest and sentence to death after she converted to Christianity, and details the differences between Christianity and the pagan Roman religions of the early third century.